INFLUENCE OF ETHICAL AND VALUE EDUCATION TOWARDS DEVELOPMENT OF STUDENTS’ LEADERSHIP SKILLS IN DELTA STATE SECONDARY SCHOOLS: AN EMPIRICAL INVESTIGATION (Journal of Association of Educational Management and Policy Practitioners, 2026)
This study examined the influence of ethical and value education towards the development of students’ leadership skills in Delta State secondary schools. Three research questions guided the study. A descriptive survey research design was employed in the study. The population for this study comprised all the 11,479 teachers from488 public secondary schools in Delta State.A purposive sampling technique was used to select 574 teachers and 244 secondary schools to ensure representation across different schools and educational zones within Delta State. The primary instrument for data collection was a researcher structured questionnaire developed based on the research purpose, containing 31 items and titled: “Influence of Ethical and Value Education towards Development of Students’ Leadership Skills Questionnaire (IEVEDSLSQ)”. The questionnaire was subjected to both face and content validation by three experts in the Department of Educational Management and Foundations from the Faculty of Education, Delta State University, Abraka. A pilot study was conducted in three secondary schools in Delta State outside the sampled area to test reliability. The score obtained after the pilot test was calculated using the Cronbach’s Alpha method to ensure internal consistency of the questionnaire which yielded coefficient values of 0.80, 0.83 and 0.89 for the three clusters respectively; and which were summed up to give an overall acceptable threshold reliability coefficient of 0.84, indicating a high level of internal consistency.Data collated were analyzed using frequencies, mean scores rated at 2.50 and standard deviation. Findings of the study generally revealed that although thatethical and value education had high positive influence on the development of students’ leadership skills in Delta State secondary schools; its integration into the curriculum was to a low extent due to several challenges.It was further discovered through one of the findings of this study that extent to which ethical and value education was integrated into the secondary school curriculum for development of students’ leadership skills in Delta State was to a low extent.From the findings of this study, recommendations were proffered. And they included among others that the Delta State Post Primary Education Board (PPEB) should ensure effective high extent of integration ethical and value education into the secondary school curriculum in every subject area such as: Social studies, Christian Religious Studies (CRS) including Islamic Religious Studies (IRS), Government, Civic/citizenship education, Security education, Business studies, Guidance and counselling including life skills programmes, hidden curriculum such as the co-curricular activities and all other pre-vocational studies, science and technology, cultural and creative arts,  for development of students’ leadership skills in Delta State. This course should be matched up with regular capacitybuilding programmes and workshops to equip teachers with the necessary skills and knowledge to effectively deliver ethical and value education in secondary schools.